Homeland Defense. U.S. Northern Command Has a Strong Exercise Program, but Involvement of Interagency Partners and States Can Be Improved - GOVERNMENT ACCOUNTABILITY OFFICE WASHINGTON DC (2009)
U.S. Northern Command (NORTHCOM) exercises to test preparedness to perform its homeland defense and civil support missions. GAO was asked to assess the extent to which NORTHCOM is (1) consistent with Department of Defense (DOD) training and exercise requirements, (2) involving interagency partners and states in its exercises, (3) using lessons learned and corrective actions to improve preparedness, and (4) integrating its exercises with the National Exercise Program (NEP). To do this, GAO reviewed NORTHCOM and NEP guidance and postexercise documentation, assessed NORTHCOM compliance, and compared DOD and NEP exercise requirements. Report to Congressional Requesters.